2020
DOI: 10.1002/jbt.22483
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of curcumin on lead‐induced hematological and hepatorenal toxicity in a rat model

Abstract: Introduction Lead (Pb) is a ubiquitous toxic heavy metal that inflicts numerous clinical consequences on humans. Curcumin is the principal component of turmeric, which is reported to have antioxidative properties. This study aimed at evaluating the ameliorative effects of curcumin on Pb‐induced hepatorenal toxicity in a rat model. Methods Thirty‐six male Sprague‐Dawley rats were randomly assigned into five groups with 12 rats in the control (normal saline) and six rats each for the lead‐treated group (LTG) (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…Also, administration of LFX (40 mg/kg BW.) daily for two weeks showed a reduction in catalase, SOD and GSH as well as rise in MDA levels in liver tissue of rats [44] 49,59]. Our results and interpretations are in agreement with aforementioned reports [14, 46, 50,].…”
Section: Vitamin E Can Help To Prevent Cholesterolrelated Endothelial Damage As Well As Functional Impairment Caused By Ros [72]supporting
confidence: 94%
See 2 more Smart Citations
“…Also, administration of LFX (40 mg/kg BW.) daily for two weeks showed a reduction in catalase, SOD and GSH as well as rise in MDA levels in liver tissue of rats [44] 49,59]. Our results and interpretations are in agreement with aforementioned reports [14, 46, 50,].…”
Section: Vitamin E Can Help To Prevent Cholesterolrelated Endothelial Damage As Well As Functional Impairment Caused By Ros [72]supporting
confidence: 94%
“…Co-supplementation of vitamin E, curcumin or ginger with LFX ameliorates the abovementioned aberrations caused by LFX toxicity; this supports the hepatorenal protective, antioxidant, and antiinflammatory properties of vitamin E, curcumin or ginger on the liver and kidney parameters [48,[55][56][57][58]. [56][57][58][59][60][61]. These results contribute antioxidant activity of vitamin E, curcumin or ginger, which inhibits the generation of free radicals in the body, neutralizes and scavenges them, and chelates prooxidant transition metals such as iron [14,20,45,62,63].…”
Section: Table (1): Effect Of Oral Administration Of Vitamin E Curcumin or Ginger On Serum Livermentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, in rat experiments with Pb accumulation in the liver and kidneys, it was shown that CUR is an effective inducer of the post-accumulation effects of oxidative toxicity. The results have shown a decrease in the Pb amount in the affected organs and the relief of degenerative changes caused by Pb [156].…”
Section: Curcumin On Lead-induced Toxicitymentioning
confidence: 85%
“…The results revealed that CUR inhibited hepatic fibrosis and liver fibrogenesis with regulation of the immune system mechanism against CCl 4 toxicity. Abubakar et al (2020) evaluated the ameliorative effects of CUR on lead (Pb)-induced hepatorenal toxicity in rats. The results showed that CUR attenuates Pb-induced hepatorenal toxicity via chelating activity and inhibition of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%